ANALIZA SWOT A MANAGEMENTULUI INOVAŢIONAL DIN CADRUL BIBLIOTECII MUNICIPALE „B.P. HASDEU” - MAMAISCAIA, Cristina (BIBLIOPOLIS, 2020)
This analysis of the innovative activity confirms the care of the Municipal Library „B.P. Hasdeu” for the innovation which is declared managerial priority. This preoccupation is confirmed by a number of innovation activities, products and services and by the feedback received from each employee’s involved in this process.